The Romano-British villa and Anglo-Saxon cemetery at Eccles, Kent : a summary of the excavations by Alex Detsicas with a consideration of the archaeological, historical and linguistic context - Stoodley, Nick (Archaeopress Archaeology, 2021)
This volume presents a study of the central and lower Medway valley during the 1st millennium AD, focusing on the 1962-1976 excavation of the Eccles Roman villa and Anglo-Saxon cemetery directed by Alex Detsicas. The author gives an account of the long history of the villa and provides a reassessment of the architectural evidence which Detsicas presented.